Robust and adaptive filtering approach to active control of noise in a cleanroom - Cai, Wenjian (2008)
In this project, active noise control technique that can be implemented in air conditioning systems are investigated. A fan-duct system is built to conduct active noise control experiments. Feedforward and feedback control algorithms with better robustness and performance are developed and implemented in the experimental system.